Frans Masereel Centrum Obra Grafica. - Frans Masereel Centrum; Amer, Biel; Forcades, Joan; Gaudaen, Gerard; Hoozee, Robert; Vanfleteren, Hilde; Weckx, Hugo (Brussel : Ministerie van de Vlaamse Gemeenschap, 1994)
Baeyens, Martin ; Bastiaensen, Jan ; Belardinello, Silvano ; Bervoets, Fred ; Bilquin, Jean ; Brazda, Jiri ; Cane, Franky ; Caymax, Katrien ; Cobbaert, Jan ; Colpin, Andre ; Cornelis, Beniti ; Cornelissen, Remy ; Courtens, Marie Antoinette ; Cremer, Jan ; Cywicki, James ; Daniels, Albert ; Dehling, Judith ; Dohmen, Walter ; Fantl, Tom ; Foster, Barbara ; Van Gestel, Fik ; Ghekiere, Joris ; Van Gisbergen, Charles ; Haccuria, Maurice ; hammond, Tom ; van den Heuvel, Hilde ; Hoenraet, Luc ; Horemans, Marc ; Hutsebaut, Achiel ; Ivens, Renaat ; De Kramer, Enk ; Kruger, Bram ; Kulhanek, Oldrich ; Lannoo, Nico ; Ledent, Ingrid ; Linden, Dirk Vander ; Loerakker, Bert ; Mahieu, Frank ; Masereel, Frans ; Mello, Richard ; Oorebeek, Willem ; Peters, Robert ; Poot, Rik ; Raveel, Roger ; Rooms, Veerle ; Ross, Conrad ; Segboer, Henk ; Stephens, Scott ; Suchanek, Vladimir ; Vandeweghe, Jan ; Verbeeck, Paul ; Vercammen, Roland ; Verstockt, Mark ; Vinck, Linda ; Walmsley, William ; Welden, Dan ; Westerveld, Gerrit ; Wisniewsky, Andrezj ; Zamiello, Craig ; Zirker, Joseph
Catalaans & Engels & Frans & Spaans
Frans Masereel Centrum Obra Grafica, Palma, març 1994
boek